Evaluation of the efficacy of FDG-PET/CT in assessing the effects of BMMSC treatment in aged rhesus monkeys - Yaohui Zhang; Jie Li; Longbao Lü; Yuanyuan Li; Zhiyu Yang; Shici Yang; Xiangqing Zhu; Rui He; Xinghua Pan; Gaohong Zhu (Stem Cell Research & Therapy)
Abstract To evaluate the therapeutic efficacy of BMMSCs in aged rhesus monkeys, histological texture features were analyzed using 18F-FDG-PET/CT imaging. The study involved three groups: five juvenile rhesus monkeys (mean age 2 years, weight 4.6 ± 0.49 kg), five young adult rhesus monkeys (mean age 6.2 ± 0.40 years, weight 3.6 ± 0.80 kg), and six aged rhesus monkeys (mean age 23.3 ± 1.37 years, weight 7.0 ± 2.77 kg). The aged group underwent 18F -FDG-PET/CT imaging at baseline, and again at 3 and 6 months following BMMSC administration. Image texture features were segmented, extracted, and analyzed using LIFEx software, with a total of 93 high-throughput PET texture features evaluated across the adolescent, young adult, and aged groups, as well as at the 3- and 6-month post-treatment time points.Significant differences (P < 0.05) in 82 texture features were observed in multiple organs, including the brain, bilateral retroocular fat, thyroid, thymus, lung, aorta, gastric sinusoids, liver, kidneys, and L4 vertebrae, across the three age groups. Comparison between the younger and older groups revealed significant differences (P < 0.05) in 31 texture features within the brain, bilateral retroocular fat, thyroid, lung, gastric sinus, left kidney, and L4 vertebrae.ROC curve analysis of the PET texture features from the thyroid, lung, gastric sinus, left kidney, and L4 vertebrae showed AUC values greater than 0.7, indicating good diagnostic performance. In aged rhesus monkeys treated with BMMSCs, PET texture features in the brain, bilateral retroocular fat, left lung, gastric sinus, and L4 vertebrae recovered to levels comparable to those of the young group at both the 3- and 6-month post-treatment time points. Additionally, histological examination via HE staining of the lung, liver, kidney, stomach, and thymus in the aged group at 6 months post-treatment revealed significant improvements in the structural integrity of these organs.These findings suggest that 18F -FDG PET texture analysis is a valuable tool for assessing the restoration of physiological function in aged rhesus monkeys following BMMSC treatment.